1977
DOI: 10.1037/0033-2909.84.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for administering creativity tests.

Abstract: Research relating to the testing conditions under which open-ended creativity tests are administered is reviewed. Wallach and Kogan's influential arguments as to the necessity for untimed game-like conditions are outlined and criticized. Conditions other than the untimed game-like condition are found to be unsatisfactory alternatives to the timed test-like condition. Finally, criteria for assessing the adequacy of various conditions are outlined. It is concluded that there is little evidence against using time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 79 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Hom 1976 andRichards 1976) is a reasonable estimate of central tendency, it must be recalled that the actual DT X IQ rs vary widely depending upon the nature of the DT tests, the heterogeneity of the sample, and apparently the nature of the testing situation. (For reviews of research dealing with this latter point, see Hattie 1977Hattie , 1980 The possibility that IQ may be a prerequisite to DT performance was proposed by Guilford (1967) and studied by examining relevant scatterplots for triangularity (Guilford 1967, Guilford & Christensen 1973, Schubert 1973, Richards 1976. While this line of investigation is far from conclusive, some DT and IQ scatterplots do seem to form a quasi-triangle compatible with Guilford's hypothesis.…”
Section: Divergent Thinking Abilities and Traditional Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Hom 1976 andRichards 1976) is a reasonable estimate of central tendency, it must be recalled that the actual DT X IQ rs vary widely depending upon the nature of the DT tests, the heterogeneity of the sample, and apparently the nature of the testing situation. (For reviews of research dealing with this latter point, see Hattie 1977Hattie , 1980 The possibility that IQ may be a prerequisite to DT performance was proposed by Guilford (1967) and studied by examining relevant scatterplots for triangularity (Guilford 1967, Guilford & Christensen 1973, Schubert 1973, Richards 1976. While this line of investigation is far from conclusive, some DT and IQ scatterplots do seem to form a quasi-triangle compatible with Guilford's hypothesis.…”
Section: Divergent Thinking Abilities and Traditional Measuresmentioning
confidence: 98%
“…TRATION A great deal of attention has been devoted in the last several years to the question of optimal DT test instructions and test conditions (see Hattie 1977Hattie , 1980 for recent reviews). Most of this work has focused on conditions needed to generate DT scores which are as weakly correlated with general intelligence measures as possible or on conditions which maxi mize raw fluency or uniqueness scores.…”
Section: The Questions Of Scoring Instructions and Test Adminismentioning
confidence: 99%
“…A review of the evidence of the importance of game-like conditions has indicated that there are no differences in the correlations between creativity and intelligence relating to the conditions of measurement (Hattie, 1977). Hattie (1980) administered five DT tests and a measure of IQ to 11-year-old students under both untimed, game-like conditions and timed, test-like conditions.…”
Section: Dt As a Criterion Of Creativitymentioning
confidence: 99%
“…Individuals' performance on instruments measuring creativity appears to be influenced by the conditions under which these instruments are administered (Beghetto, 2005;Hattie, 1977Hattie, , 1980Plucker & Renzulli, 1999;Runco & Albert, 1985;). …”
Section: Testing Conditionsmentioning
confidence: 99%
“…There has been a great deal of research on the optimal conditions for administering creativity instruments (see Chen et al, 2005;Hattie 1977;Lemons, 2011). This body of research has been concerned with comparing different testing conditions, including atmosphere (test-like vs. game-like), time limit (timed vs. untimed), setting (individual vs. group) and instruction (explicit "be creative" vs. standard) (Plucker & Renzulli, 1999).…”
Section: Testing Conditionsmentioning
confidence: 99%